The evolution of cephalic fins in manta rays and their relatives: functional evidence for initiation of domain splitting and modulation of the Wnt signaling pathway in the pectoral fin AER of the little skate - Emily P. McFarland; Karen D. Crow (EvoDevo)
Abstract Background Batoids possess a unique body plan associated with a benthic lifestyle that includes dorsoventral compression and anteriorly expanded pectoral fins that fuse to the rostrum. The family Myliobatidae, including manta rays and their relatives, exhibit further modifications associated with invasion of the pelagic environment, and the evolution of underwater flight. Notably, the pectoral fins are split into two domains with independent functions that are optimized for feeding and oscillatory locomotion. Paired fin outgrowth is maintained during development by Wnt3, while domain splitting is accomplished by expression of the Wnt antagonist Dkk1, which is differentially expressed in the developing anterior pectoral fins of myliobatids, where cephalic fins separate from pectoral fins. We examine the evolution of this unique feature in the cownose ray (Rhinoptera bonasus), a member of the genus that is sister to Mobula. Results Here, we provide functional evidence that DKK1 is sufficient to initiate pectoral fin domain splitting. Agarose beads soaked in DKK1 protein were implanted in the pectoral fins of little skate (Leucoraja erinacea) embryos resulting in AER interruption. This disruption arrests fin ray outgrowth, resembling the myliobatid phenotype. In addition, fins that received DKK1 beads exhibit interruption of Axin2 expression, a downstream target of β-catenin-dependent Wnt signaling and a known AER marker. We demonstrate that Msx1 and Lhx2 are also associated with fin expansion at the AER. These results provide functional evidence for the underlying genetic pathway associated with the evolution of a novel paired fin/limb modification in manta rays and their relatives. We introduce the gas/brake pedal model for paired fin remodeling at the AER, which may have been co-opted from domain splitting in pelvic fins of cartilaginous fishes 370 million years earlier. Conclusions The pectoral fins of manta rays and their relatives represent a dramatic remodel of the ancestral batoid body plan. The premiere feature of this remodel is the cephalic fins, which evolved via domain splitting of the anterior pectoral fins through inhibition of fin ray outgrowth. Here, we functionally validate the role of Dkk1 in the evolution of this phenotype. We find that introduction of ectopic DKK1 is sufficient to recapitulate the myliobatid pectoral fin phenotype in an outgroup lacking cephalic fins via AER interruption and fin ray truncation. Additional gene expression data obtained via in situ hybridization suggests that cephalic fin development may have evolved as a co-option of the pathway specifying claspers as modifications to the pelvic fins, the only other known example of domain splitting in vertebrate appendages.